Profile of Glioma Patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, 2018-2022 - Rizki Ahmad Fauzan; Djohan Ardiansyah; Dyah Fauziah; Yudha Haryono (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2026)
Highlights: This study provides updated insights into glioma profiles in Indonesia, focusing on a large patient cohort from a major referral hospital. Most gliomas were large tumors located in the cerebrum, with midline shift and heterogeneous contrast enhancement being the primary radiological features observed. Glioblastoma was the predominant type, yet no significant correlation was found between radiological features and histopathological grading, highlighting a potential gap in predictive diagnostics.   Abstract Introduction: Glioma is a common brain tumor that significantly impacts patients’ quality of life by affecting motor, sensory, cognitive, and emotional functions. This study aimed to provide a holistic and comprehensive analysis of glioma characteristics by examining clinical, radiological, and histopathological data from patients treated at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, over five years from 2018 to 2022. Methods: This retrospective cross-sectional study analyzed records of 204 glioma patients from Dr. Soetomo General Academic Hospital, Surabaya, Indonesia (2018-2022). Data included demographics, clinical symptoms, tumor size and location, radiological features, and histopathological grading. Statistical analysis used Fisher’s exact test (p<0.05), and data were processed using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 23.0. Results: The most affected age group was 30-39 years old (19.1%), and it was predominantly male (59.8%). Headache was the most common presenting symptom (33.8%). Tumors were predominantly located in the cerebrum (75.9%), and most lesions measured >4 cm (76.9%). Midline shift was observed in 69.1% of cases. Contrast enhancement was described as heterogeneous in 35.8% and homogeneous in 1.5%, while 62.7% of cases lacked enhancement data. Histopathologically, the World Health Organization (WHO) grade 4 gliomas (glioblastoma) were the most frequent (39.22%). No significant association was found between radiological features (midline shift or contrast enhancement) and histopathological grading (p>0.05). Conclusion: Gliomas were predominantly found in male patients and were most common among individuals in their younger adult years. The primary clinical symptom was headache, with tumors frequently located in the cerebrum and typically presenting as large masses. Histopathologically, glioblastoma represented the most frequent and aggressive type identified.